Autologous chondrocyte grafting promotes bone formation in the posterolateral spine. Issue 1 (23rd March 2018) - Sielatycki, J. Alex; Saito, Masanori; Yuasa, Masato; Moore‐Lotridge, Stephanie N.; Uppuganti, Sasidhar; Colazo, Juan M.; Hysong, Alexander A.; Robinette, J. Patton; Okawa, Atsushi; Yoshii, Toshitaka; Schwartz, Herbert S.; Nyman, Jeffry S.; et al.
Abstract : Background context: Pseudarthrosis following spinal fusion remains problematic despite modern surgical and grafting techniques. In surgical spinal fusion, new bone forms via intramembranous and endochondral ossification, with endochondral ossification occurring in the hypoxic zones of the fusion bed. During bone development and fracture healing, the key cellular mediator of endochondral ossification is the hypertrophic chondrocyte given its ability to function in hypoxia and induce neovascularization and ossification. We therefore hypothesize that hypertrophic chondrocytes may be an effective bone graft alternative. Purpose: Spinal fusion procedures have increased substantially; yet 5% to 35% of all spinal fusions may result in pseudoarthrosis. Pseudoarthrosis may occur because of implant failure, infection, or biological failure, among other reasons. Advances in surgical techniques and bone grafting have improved fusion; however pseudarthrosis rates remain unacceptably high. Thus, the goal of this study is to investigate hypertrophic chondrocytes as a potential biological graft alternative. Methods: Using a validated murine fracture model, hypertrophic chondrocytes were harvested from fracture calluses and transplanted into the posterolateral spines of identical mice. New bone formation was assessed by X‐ray, microcomputed tomography (μCT), and in vivo fluorescent imaging. Results were compared against a standard iliac crest bone graft and a sham surgery control group. Funding for this work was provided by the Department of Orthopaedics and Rehabilitation, the OREF (Grant #16‐150), and The Caitlin Lovejoy Fund. Results: Radiography, μCT, and in vivo fluorescent imaging demonstrated that hypertrophic chondrocytes promoted bone formation at rates equivalent to iliac crest autograft. Additionally, μCT analysis demonstrated similar fusion rates in a subset of mice from the iliac crest and hypertrophic chondrocyte groups. Conclusions: This proof‐of‐concept study indicates that hypertrophic chondrocytes can promote bone formation comparable to iliac crest bone graft. These findings provide the foundation for future studies to investigate the potential therapeutic use of hypertrophic chondrocytes in spinal fusion. Abstract : The work presented here is the first to investigate the efficacy of hypertrophic chondrocytes, the key cellular mediators of endochondral ossification, for augmentation of bone formation in the posterior region of the lumbar spine. These results support the hypothesis that hypertrophic chondrocytes can promote bone formation at comparable rates to iliac crest bone grafts, and thereby may serve as a potential graft alternative. These preclinical studies provide the foundation and proof‐of‐concept for further transnational work aimed at transitioning these findings to clinical use.